Entrepreneurial behavior of large cardamom growers: A case study in Lamjung district of Nepal - Shrestha, Srijana; Pandey, Bishnu; Joshi, Narayan Raj; Shrestha, Jiban; Timsina, Krishna Prasad (Journal of Agriculture and Natural Resources, 2020)
Study on entrepreneurial behavior of large cardamom growers in Lamjung District, Nepal was conducted from December 2017 to June 2018 in Marshyangdi Rural Municipality of Lamjung district. The Rural Municipality was selected purposely for the study due to the recent establishment of Cardamom Zone under the Prime Minister Agriculture Modernization Project in the Municipality focusing on large cardamom development. Altogether 80 large cardamom growers were selected randomly from 454 large cardamom growers of the study site. Data were collected through household surveys, focus group discussions, key informant interviews, personal observations, and other secondary sources. Results showed that a greater proportion of large cardamom growers were found to have medium level of innovativeness (45%), decision-making ability (51.2%), information-seeking ability (48.8%), risk orientation (46.2%), leadership ability (43.8%), achievement motivation (46.2%) and low management orientation (56.3%) which contributed to the overall medium entrepreneurial behavior (47.5%) of large cardamom growers in the study area. About 35 percent of farmers were belonging to the low entrepreneurial behavior and only a few numbers of farmers (17.5%) were under the high entrepreneurial behavior category. The high number of farmers with low and medium entrepreneurial behavior and a low number of farmers with high entrepreneurial behavior has resulted in poor commercialization of large cardamom in the study area. Educational status, landholding, extension participation, economic motivation, experience in large cardamom farming, and area of large cardamom cultivation were found to have a significant correlation with the entrepreneurial behavior of large cardamom farmers while age had a negative and significant effect. There is still scope to increase the number of large cardamom farmers with high entrepreneur behavior for commercializing large cardamom in the study area but programs should be designed and implemented accordingly.